2016
DOI: 10.2224/sbp.2016.44.9.1429
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of School Readiness Between Rural and Urban Chinese Preschool Children

Abstract: Children's future academic success may depend on their readiness to learn and participate in preschool education. We examined school readiness differences in a sample of rural and urban preschool children (N = 82) from Zunyi, China, using the School Readiness Test Battery. The results indicated that school readiness differed between rural and urban children; rural children scored lower on emotional and social skills, basic knowledge, and drawing and language competence subtests than did urban students, but hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…The study has empirically demonstrated that rural children are less prepared for primary school than children in urban areas in pre-academic skills (pre-literacy and pre-mathematics), executive function and socioemotional cognition. This is in agreement with previous studies done in Peru (Castro & Rollstone, 2015), Chile (Förster M. & Rojas-Barahona, 2014), China (Gan & Meng, 2016) and Argentina (Hermida et al, 2019). This concurrence implies that despite the sociocultural differences associated with various countries, urban children perform better than rural children in academic and cognitive tasks.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The study has empirically demonstrated that rural children are less prepared for primary school than children in urban areas in pre-academic skills (pre-literacy and pre-mathematics), executive function and socioemotional cognition. This is in agreement with previous studies done in Peru (Castro & Rollstone, 2015), Chile (Förster M. & Rojas-Barahona, 2014), China (Gan & Meng, 2016) and Argentina (Hermida et al, 2019). This concurrence implies that despite the sociocultural differences associated with various countries, urban children perform better than rural children in academic and cognitive tasks.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous findings that have compared performance of rural and urban children in academic and cognitive tasks. For example, in Peru (Castro & Rollstone, 2015), Chile (Förster M. & Rojas-Barahona, 2014), China (Gan & Meng, 2016) and Argentina (Hermida et al, 2019) urban pre-school children than consistently scored here on learning tasks than rural children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors related to school readiness were: urban versus rural environment, with children from urban areas proving better adjustment than those from rural areas (Gan, Meng, & Xie, 2016;Bailey, 2014), bilingualism, with bilingual children rated higher on school readiness (Guhn, Milbrath, &Hertzman, 2011).…”
Section: School Readiness and Adjustment In Children: The Need For A mentioning
confidence: 99%
“…The initial discussion focused on inequity of circumstance between eastern and western development. However, rural disparity has more recently emerged in research as the most prominent factor driving inequity (Gan, Meng, & Xie, 2016;Golley & Kong, 2016;Hallinger & Liu, 2016;Li & Ranieri, 2013;Normile, 2017;Rao & Ye, 2016;Wang, Wang, Li, Li, 2017;Wu, 2013;Yang & Wan, 2015;Zhou et al, 2015), describing the issue as a more serious dilemma affecting both eastern and western regions of China.…”
Section: Introductionmentioning
confidence: 99%